Состояние и проблемы развития радиоэлектронной отрасли Украины - Demedyuk, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
An analysis is carried out of the development of the electronic instrument and machine engineering sectors in Ukraine after 1991. The problems are listed, the solution of which would contribute to the creation of industrial, household, and specialized equipment that meets the world standard.